1968
DOI: 10.1007/bf02279190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disuse osteoporosis on bone composition: the fate of bone matrix

Abstract: Disuse bone atrophy was induced in 10 adult dogs by means of brachial plexus section and/or elbow disarticulation. After 9 to 12 weeks of disuse intact humeri were examined by X-ray, and their physical properties determined. The whole humeri were isolated, defatted, dried to constant weight, and their mineral and collagen content determined.Eight out of 10 experimental (non-ueed) humeri demonstrated evidence of decreased radiodensity. The non-used limb demonstrated parallel loss in dry, fat-free weight (--23.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Sciatic neurectomy (SNR) has been reported as a means of inducing severe osteoporosis [26,27]. As in previous studies, we also demonstrated significantly lower bone density in the proximal tibiae from 10 days after SNR than in sham-operated mice by μCT (Fig.…”
Section: Sciatic Neurectomy Reduces Bone Density While Increasing Aresupporting
confidence: 79%
See 1 more Smart Citation
“…Sciatic neurectomy (SNR) has been reported as a means of inducing severe osteoporosis [26,27]. As in previous studies, we also demonstrated significantly lower bone density in the proximal tibiae from 10 days after SNR than in sham-operated mice by μCT (Fig.…”
Section: Sciatic Neurectomy Reduces Bone Density While Increasing Aresupporting
confidence: 79%
“…Ten-week-old female C57BL/6 mice were subjected to unilateral sciatic neurectomy (SNR) or sham surgery (day 0) under isoflurane-induced anesthesia. SNR consisted of resecting a 3-to 4-mm segment of the right sciatic nerve posterior to the hip joint [26,27]. For sham surgery, the same procedure was performed without resection.…”
Section: Image Analysismentioning
confidence: 99%
“…Our initial report on disuse induced by disarticulation in dogs (14) did not measure the effect of disuse on soft tissues. The present study attempts to correlate collagen resorption and net mass in soft tissues with bone-ligament-bone strength, and bone resorption and net mass of bone in an ankle disarticulated model of immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the work of several investigators has suggested that during the development of disuse osteoporosis, bone resorption is accelerated, while lation. Disuse osteoporosis can be produced in laboratory animals by the immobilization of an extremity through casting, denervation, or a combination of the two (1,4,(6)(7)(8)(9)(10)(11)(12)15,17,18,(20)(21)(22)(23)(24)26,27). In rats a reproducible osteoporosis develops in the ipsilateral tibia over 28 days following sciatic denervation (4,5, 25).…”
mentioning
confidence: 99%